2023
DOI: 10.1002/edn3.380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of an eDNA metabarcoding assay for detection of freshwater myxozoan communities

Abstract: The environmental DNA (eDNA) metabarcoding approach has become a useful tool for detecting the species diversity of different animal groups, including parasites.Myxozoa (Malacosporea and Myxosporea) represent a unique group of morphologically simplified endoparasites that mainly infest fish and whose diversity remains largely unexplored. Metabarcoding of DNA from the aquatic environment is a promising non-invasive method that allows us to assess myxozoan biodiversity at a given site. This is essential not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…This method increased the myxozoan prevalence detection up to 6 ×, representing 3.7 × more species detected by PCR screening than by microscopy; this represents nearly 1.3 × higher than a recent similar screening of fish tissues from the Czech Republic (2.8 ×). In this same study, a newly developed eDNA metabarcoding assay was shown to capture up to 2.5 × more diversity than PCR and Sanger sequencing in fish tissue 44 . The molecular screening carried in this study represents a useful tool for myxozoan diversity exploration and can be used for preliminary screening of fish tissue, representing a less intensive labor method than microscopy screening and a more accessible/less complex methodology than eDNA metabarcoding.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This method increased the myxozoan prevalence detection up to 6 ×, representing 3.7 × more species detected by PCR screening than by microscopy; this represents nearly 1.3 × higher than a recent similar screening of fish tissues from the Czech Republic (2.8 ×). In this same study, a newly developed eDNA metabarcoding assay was shown to capture up to 2.5 × more diversity than PCR and Sanger sequencing in fish tissue 44 . The molecular screening carried in this study represents a useful tool for myxozoan diversity exploration and can be used for preliminary screening of fish tissue, representing a less intensive labor method than microscopy screening and a more accessible/less complex methodology than eDNA metabarcoding.…”
Section: Discussionmentioning
confidence: 90%
“…However, eDNA metabarcoding assays of myxozoans may provide a closer to reality biodiversity estimation, especially when using fish tissues. Lisnerová et al 44 also demonstrated the effectivity of these assays when applied to sediment samples, as a non-invasive (no fish sacrifice) technique. This could represent an excellent alternative for future myxozoan diversity estimation in Mexico, where many fish species are rare, threatened or endangered.…”
Section: Discussionmentioning
confidence: 97%